Print's best letterheads & business cards 6 : winning designs from Print magazine's national design competition - Dover, Caitlin (RC Publications, 2000)
Distinctive letterheads and business cards still pack a punch in today's business world, despite the growing popularity of cyber communications. PRINT's Best Letterheads & Business Cards 6 presents over 100 examples of stationery culled from recent editions of PRINT magazine's Regional Design Annual. An indispens-able reference for any designer, this collection offers a fresh take on the ever-evolv-ing realm of stationery design, and explores the process by which the featured designers arrive at their winning visual solutions. The book is divided into seven categories: Retail/Products/Manufacturers, Technology, Creative Services, Entertainment, Services, Non-Profits & Special Events, and Design Firms. Each section is accompanied by an introduction that includes information about the creation of individual projects: initial concepts, working methods, printing processes used, costs, and client response.